Description The Level of Anxiety in Pre-Operation Patients - Amanda Sri Utari; Susanto, Amin; Sumarni, Tri (Java Nursing Journal, 2024)
Background: Preoperative anxiety is a common psychological response in patients awaiting surgery, potentially influencing perioperative outcomes and recovery. Purpose: This study aims to assess the levels of anxiety experienced by preoperative patients at Dr. Soedirman Kebumen General Hospital. Methods: A descriptive, quantitative cross-sectional design was employed, involving 84 patients selected through purposive sampling. The study collected demographic data, including gender, age, and education level, alongside medical data such as the type of anesthesia and prior surgical experience. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. Findings: Showed that 4 patients (4.8%) experienced mild anxiety, 66 patients (78.6%) had moderate anxiety, 12 patients (14.3%) exhibited severe anxiety, and 2 patients (2.4%) reported extreme anxiety or panic. The study revealed that the majority of patients (78.6%) undergoing surgery at Dr. Soedirman Kebumen General Hospital experienced moderate anxiety levels, suggesting the need for improved preoperative support and intervention strategies. Addressing patient anxiety could enhance perioperative success by reducing psychological distress and improving overall patient outcomes. Conclusions: Further studies should explore the effectiveness of targeted interventions to mitigate preoperative anxiety and its impact on surgical recovery.